The development of the Quality Indicator for Rehabilitative Care (QuIRC): a measure of best practice for facilities for people with longer term mental health problems - Almeida, José Miguel Barros Caldas de (2011)
Background: Despite the progress over recent decades in developing community mental health services internationally, many people still receive treatment and care in institutional settings. Those most likely to reside longest in these facilities have the most complex mental health problems and are at most risk of potential abuses of care and exploitation. This study aimed to develop an international, standardised toolkit to assess the quality of care in longer term hospital and community based mental health units, including the degree to which human rights, social inclusion and autonomy are promoted. Method: The domains of care included in the toolkit were identified from a systematic literature review, international expert Delphi exercise, and review of care standards in ten European countries. The draft toolkit comprised 154 questions for unit managers. Inter-rater reliability was tested in 202 units across ten countries at different stages of deinstitutionalisation and development of community mental health services. Exploratory factor analysis was used to corroborate the allocation of items to domains. Feedback from those using the toolkit was collected about its usefulness and ease of completion. Results: The toolkit had excellent inter-rater reliability and few items with narrow spread of response. Unit managers found the content highly relevant and were able to complete it in around 90 minutes. Minimal refinement was required and the final version comprised 145 questions assessing seven domains of care. Conclusions: Triangulation of qualitative and quantitative evidence directed the development of a robust and comprehensive international quality assessment toolkit for units in highly variable socioeconomic and political contexts.